Juridical Review of the Authority of the House of Representatives in Proposing the Dismissal of Constitutional Judges is Associated with the Principle of Legal Certainty and Does Not Abuse Authority in the General Principles of Good Government - Govin Genaro Sihotang; Demson Tiopan (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This article discusses the authority of the House of Representatives in proposing the dismissal of Constitutional Court judges. This analysis is associated with Article 23 of Law Number 7 of 2020 concerning the Third Amendment to Law Number 24 of 2003 concerning the Constitutional Court. This legal research is based on qualitative methodology using literature studies sourced from laws and regulations, books, and scientific journal articles. This article concludes that the House of Representatives is only authorized to propose 3 (Three) constitutional judges in accordance with applicable regulations and is not authorized to propose the dismissal of Constitutional Court judges because there are no legal rules that can be based on the House of Representatives to propose the dismissal of Constitutional Court judges. The reason for the House of Representatives in proposing the dismissal is only based on certain political reasons, namely Aswanto as a constitutional judge often annuls the legal products of the House of Representatives, which is certainly the task of a constitutional judge to examine the law against the Constitution, associated with the General Principles of Good Governance, the steps of the House of Representatives are not in accordance with the principle of legal certainty and the principle of not abusing authority. In this case, the House of Representatives should not override its own products. This article discusses the authority of the House of Representatives in proposing the dismissal of Constitutional Court judges. This analysis is associated with Article 23 of Law Number 7 of 2020 concerning the Third Amendment to Law Number 24 of 2003 concerning the Constitutional Court. This legal research is based on qualitative methodology using literature studies sourced from laws and regulations, books, scientific journal articles